Dimensional Control of Highly Anisotropic and Transparent Conductive Coordination Polymers for Solution-Processable Large-Scale 2D Sheets - Suh, Bong Lim (Advanced materials (Deerfield Beach, Fla.), 2023)
© 2022 The Authors. Advanced Materials published by Wiley-VCH GmbH.